The Devolutionist and the Emancipatrix - Flint, Homer Eon, 1888-1924 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Devolutionist and the Emancipatrix" by Homer Eon Flint is a science fiction novel likely written in the early 20th century. This book explores themes of telepathy, exploration, and societal structures as it follows Dr. William Kinney and a group of explorers who experiment with telepathically connecting to unknown beings, specifically those on other planets like Venus and Mercury. At the start of the narrative, a mysterious scene unfolds in Dr. Kinney's study, where he and three other individuals are found in a state of induced sleep, connected by wires and bracelets. The story quickly shifts to Mr. Hill, a friend of the doctor, who learns about the astounding results of a recent journey through space undertaken by Dr. Kinney and his companions. They returned with extraordinary findings, including advanced civilizations on Venus that engage in telepathy. As the narrative progresses, the explorers prepare for more experiments, aiming to expand their understanding of the universe and its inhabitants, setting the stage for an intricate interplay between exploration, social commentary, and individual agency. (This is an automatically generated summary.)
The devolutionist -- The emancipatrix.
Release date is 2004-06-01
Charles Franks and the Online Distributed Proofreading Team
Keywords: Science fiction; Life on other planets -- Fiction